Development and application of microfluidic sweat detection technology in mental health monitoring - Danni Zhao; Ran Chen; Shuyue Jiang; Weiwei Xie; Kaihuan Zhang; Jianlong Zhao; Shilun Feng; Shengtai Bian (View)
Abstract Mental health significantly affects individuals' thoughts and behaviors, making its monitoring crucial in high‐stakes environments like truck driving and space missions. Traditional wearable sensors often focus on physiological indicators such as heart rate, but microfluidic wearable sensors offer a promising alternative by enabling precise, quantitative analysis of sweat biomarkers. This review explores recent advancements in microfluidic wearable sensors for mental health monitoring, highlighting their ability to analyze biomarkers such as stress hormones, dopamine, and catecholamines. We discuss the development, application methods, and challenges of these sensors, as well as their future prospects in mental health monitoring.